2008 47th IEEE Conference on Decision and Control 2008
DOI: 10.1109/cdc.2008.4739306
|View full text |Cite
|
Sign up to set email alerts
|

Predictive compensation for communication outages in networked control systems

Abstract: Abstract-A predictive outage compensator co-located with the actuator node in a networked control system can be used to counteract unpredictable losses of data in the feedback control loop. When a new control command is not received at the actuator node at an appropriate time instance, the predictive outage compensator suggests a replacement command based on the history of past control commands. It is shown that a simple tuning phase together with the monitoring of the control history can lead to a compensator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…The above discussions indicate that the underlying plant dynamics is given by (6) in the nominal mode, (16) in the skip mode, and (19) in the abort mode. Suppose, in general, starting at k, there are i instants of nominals, followed by j skip instants (each with a length of 2h), followed by r instants of aborts, for = 1 : p, with…”
Section: B Implementation Of the Overrun Frameworkmentioning
confidence: 96%
“…The above discussions indicate that the underlying plant dynamics is given by (6) in the nominal mode, (16) in the skip mode, and (19) in the abort mode. Suppose, in general, starting at k, there are i instants of nominals, followed by j skip instants (each with a length of 2h), followed by r instants of aborts, for = 1 : p, with…”
Section: B Implementation Of the Overrun Frameworkmentioning
confidence: 96%
“…It turns out that it is then possible to use that solution to bound the second term, and thus to bound the error criterion (13).…”
Section: A Hankel Approximation Ofmentioning
confidence: 99%
“…Predictive control has been extensively used in various networked control settings, e.g., [11], [12]. The POC was introduced in [13], where we showed that a fairly simple filter significantly could improve the performance of control systems under communication outages.…”
Section: Introductionmentioning
confidence: 99%
“…The presented strategy assumes an upper bound on the consecutive faults and zero sensor-to-actuator delay. A more recent approach to handle dropped signals in a networked control system is the predictive outage control presented in [4]. This approach is based on predictive form and was implemented using an additional computational block next to the actuator to compute new input signals in case no new messages arrived.…”
Section: A Related Workmentioning
confidence: 99%